HEAD AND NECK SQUAMOUS CELL CARCINOMA DEPENDING ON THE MORPHOLOGICAL CHARACTERISTICS OF THE PRIMARY TUMOR - V. A. Bychkov; L. N. Bondar; E. L. Choynzonov; V. M. Perelmuter (Сибирский онкологический журнал)
Objective: to analyze the association of 5 types of cellular structures of squamous cell carcinoma with major clinical and morphological tumor characteristics. Material And Methods. The main clinical and morphological characteristics of the primary tumor were assessed in 74 patients. Results. Single tumor cells and structures formed by polymorphic cells were observed in primary tumor more often in the patients with metastatic lymph nodes than in patients with intact lymph nodes. Furthermore, inflammatory reaction in the patients with metastatic lymph nodes was significantly lower than in the patients with intact lymph nodes.Conclusion. Morphological heterogeneity of the tumor allows us to suggest the clinical course of the head and neck squamous cell carcinoma.